Self-processes, learning, and enabling human potential : dynamic new approaches - Marsh, Herbert W. (Herbert Warren); Craven, Rhonda; McInerney, D. M., (Dennis M.), 1948- (Charlotte, NC : Information Age Publishing, 2008)
32